Sosialisasi Pengelolaan UMKM dan Pembuatan Video Promosi UMKM untuk Website Desa Karangkuten - Agus Sunaryo; Sinta Restu Ningsih; Sri Puji Astutik; Arini Setiawati; Sal Sabila Afiatul Uma; Lusi Abela Dwi Anisa6; Erin Rahmawati; Rokhmat Hidayat; Yogi Firmansyah; Lila Maulida Sibrina; Nindi Fernika Febriana; Muhammad Fahrul Andimas; Mohammad Rusydi Abdul Malik; Nely Ratna Dila; Syauqi Baldan Sururi; Siti Alfa Dita Lailatul Rohmah; Muhammad Azzahri Zeaul Al Haq; Solikan Solikan; Nafissastul Ghunyah; Restina Puja Fatmawati; Dia Sandia Arini; Sri Amelia; Della Fristina; Alifia Zulfa Anaida; Finanshe Daya Trinada; Firman Hariyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are one of the key pillars of the rural economy, including in Karangkuten Village. Although they exist in significant numbers and possess considerable economic potential, most rural MSMEs still face various limitations in the marketing aspect, particularly in utilizing rapidly developing digital media. This Community Service Program (KKN) of the Faculty of Economics aims to support the digitalization process of MSMEs through the creation of engaging promotional videos integrated with the official website of Karangkuten Village. The implementation method of this program includes stages of socialization for MSME actors, video recording in six hamlets, a systematic editing process, as well as uploading and handing over the results to the village government. The results of the activity indicate that this program successfully produced MSME promotional video content that is not only engaging and informative but also suitable for publication on the village website as a digital promotional medium. In addition to increasing the visibility and branding of MSMEs, this program also contributes to strengthening the image of Karangkuten Village as a culinary village and a center for innovative creative MSMEs. This program is expected to provide long-term impacts in improving the competitiveness of MSMEs and encouraging sustainable and inclusive rural economic growth.